HUMANKIND VERSUS OTHERS-IN-LAW: Re-Visioning Levinas for a Postmodern Hierophany - Abraham, T J (Journal of Dharma, 2009)
Perhaps, the core of the philosophy of Emmanuel Levinas can best be termed as "one's absolute responsibility for the other" where the other unequivocally stands for human beings: Hence, one is unlikely to be wide of the mark, if Levinasian ethics, with some qualification, is designated as 'humanist'. Yet, to be labelled as a 'humanist' in the period during and after the second halfofthe zo" century is not altogether laudatory, For, the Enlightenment humanist project, generally believed to be an offshoot of the Cartesian Cogito, stands discredited consequent on the rude jolt administered by the anti-essentialist and anti-humanist poststructuralist upsurge, The human centrality was problematized and sidelined in the new philosophies contemporaneous with the Levinasian heyday, Vigorous ecological concerns, upon the heels of these philosophies, have not been comfortable with the exclusionary focus on 'man', due to the growing realization of the interdependence of the human and the nonhuman spheres, Deep ecologists justly accuse the 'environmentalists' as being narcissistically obsessed with the future 'human' welfare, and less with the happiness of alL For, environment is invariably taken to be a humancentred one,